2020
DOI: 10.7717/peerj.10181
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of SARS-CoV-2 nsp14 exhibit strong association with increased genome-wide mutation load

Abstract: SARS-CoV-2 is a betacoronavirus responsible for COVID-19, a pandemic with global impact that first emerged in late 2019. Since then, the viral genome has shown considerable variance as the disease spread across the world, in part due to the zoonotic origins of the virus and the human host adaptation process. As a virus with an RNA genome that codes for its own genomic replication proteins, mutations in these proteins can significantly impact the variance rate of the genome, affecting both the survival and infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…The mutation that most strongly affects the mutation density was the 14408C > T mutation, predicating it as a genotype of interest. In our follow-up study, we also identified the trend of a positive correlation between the presence of the 14408C > T mutation and increased mutation density in regions under low selective pressure persisted beyond our initial study ( Eskier et al, 2020c ).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…The mutation that most strongly affects the mutation density was the 14408C > T mutation, predicating it as a genotype of interest. In our follow-up study, we also identified the trend of a positive correlation between the presence of the 14408C > T mutation and increased mutation density in regions under low selective pressure persisted beyond our initial study ( Eskier et al, 2020c ).…”
Section: Introductionsupporting
confidence: 52%
“…RdRp is one of the SARS-CoV-2 proteins responsible for replicating the viral genome, and it is expected that mutations in its sequence and structure might lead to a change in overall mutation rates, as we have shown in previous studies ( Eskier et al, 2020b , Eskier et al, 2020c ). It is less clear how the D614G mutation in the S gene could affect the mutation rate; however, increased transmission across the population might lead to more permissive circumstances for novel mutations to arise.…”
Section: Discussionmentioning
confidence: 58%
“…These mutations occur despite the exonuclease corrective activity (NSP14) and are associated with selection pressure induced by host immune response and vaccine/therapeutic immunity or tissue differentiation. Among these mutations, some are linked to the immune system, particularly when present in the RBD, such as E484K and S477N [ 23 , 24 ]. It has also been shown that mutations in RNA-dependent RNA polymerase (RdRp), particularly the P323 mutation in Nsp12 initially observed in the D614G variant, accelerate RdRp, thus affecting its fidelity and promoting mutations in the viral structural proteins [ 25 ].…”
Section: Genetic Variabilitymentioning
confidence: 99%
“…To mitigate the low fidelity of RdRp, all coronaviruses encode a 3’-to-5’ exoribonuclease (ExoN) in nsp14 ( 10 12 ). Mutations of SARS-CoV-2 nsp14 exhibit strong association with increased genome-wide mutation load ( 13 , 14 ), and genetic inactivation of ExoN in engineered SARS-CoV and murine hepatitis virus (MHV) leads to 15 to 20-fold increases in mutation rates ( 7 , 15 , 16 ). Furthermore, in a mouse model, SARS-CoV with inactivated ExoN shows a mutator phenotype with decreased fitness and lower virulence over serial passage, suggesting a potential strategy for generating a live, impaired-fidelity coronavirus vaccine ( 17 ).…”
Section: Introductionmentioning
confidence: 99%